Body mass index and risk of malnutrition in community-living elderly men and women: relationships with morbidity, mortality and health- related quality of life. The Tromsø and HUNT studies - Kvamme, Jan-Magnus (European Journal of Epidemiology, 2011)
The elderly population is rapidly growing, and elderly individuals are more vulnerable to nutritional problems than other adults. A number of studies have found evidence for adverse health outcomes in elderly patients at risk of malnutrition. However, much of the previous research has been performed in hospital populations or in groups of elderly patients with specific diagnoses. More population-based studies in this area are therefore needed. Increased understanding of nutrition in elderly individuals can contribute to the identification of individuals at risk of malnutrition at an earlier stage. Based on data from three large health surveys, we aimed to study the relationship between nutritional status and important health outcomes in community-living elderly individuals. We first explored the associations between disease burden, social and life style variables in a crosssectional design based on data from the Tromsø 4 survey (1994-1995) (paper I). We found that fractures (hip), mental distress, reduced muscle strength and current smoking were more prevalent in underweight individuals. Chronic lung disease and reduced physical activity had a U-shaped relation with body mass index (BMI). Diabetes and ischemic heart disease were more prevalent in obese individuals. In the Tromsø 6 survey (2007-08), we included the Malnutrition Universal Screening Tool (MUST). We found that approximately 8% of this community-living population was at medium or high risk of malnutrition and that 20% was obese (BMI >30 kg/m2). We used a cross-sectional design to explore the association between mental health symptoms and both risk of malnutrition and BMI (paper II). Mental health symptoms were significantly associated with the risk of malnutrition, and an association was also found for subthreshold mental health symptoms. Quality of Life is an important health aspect for the increasing number of elderly individuals with longer life expectancy. We found a significant reduction in Health-related Quality of Life with an increasing ...